Evolution of unregulated hydrocarbons distribution with different post injection strategies in a common-rail diesel engine. (1st May 2022) - Lei, Lili; Wu, Yan; Muhammad Farhan, Sheikh; Bai, Shuzhan; Wang, Pan
Highlights: With closed post injection, post-combustion hinders the HCs species accumulation. A delay in the peak emissions exists between lighter HCs and heavier HCs. As the carbon chain grows, Alkanes and olefins show opposite evolution rules. Under post injection operation, NC8 species accounts for the majority in all tests. Abstract: The experiments were carried out to investigate the influence of different post injection timing and post injection rate on the performance of combustion and unregulated hydrocarbons species emissions from a common-rail diesel engine. Fourier transform infrared spectroscopy was used to measure and analyze the unregulated hydrocarbons emissions which include light hydrocarbons (HCs), aromatic hydrocarbon (AHC), and n-octane (NC8 ). The results showed that the emissions of individual hydrocarbon species were the similar to that of single injection when the post injection time was at 20 °CA and 40 °CA. In the measured hydrocarbons components, CH4 and C4 H6 species maintained a low level and weak sensitivity to the different post injection conditions. The overall variation of NC8 species emission was similar to that of THC emission and accounted for most of the THC, which indicated that most of the fuel had no chemical change and entered the exhaust directly under different post injection conditions. It should be noticed that the olefin species decreased and the alkane species increased gradually as the HCs species raised from C1 to C4. Furthermore, the distribution of HC species at 60 °CA was less changed than that of 40 °CA under different post injection rates and was closer to the required after-treatment gas atmosphere due to its larger proportion of highly reactive components.